2013
DOI: 10.1111/jre.12039
|View full text |Cite
|
Sign up to set email alerts
|

Subepithelial connective tissue graft with or without enamel matrix derivative for the treatment of Miller class I and II gingival recessions: a controlled randomized clinical trial

Abstract: The present study failed to demonstrate any additional clinical benefits when EMD was added to SCTG plus CAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 47 publications
6
50
1
8
Order By: Relevance
“…Individual patient data (IPD) were provided by the author and re‐analysed to obtain mean difference for VAS Est. Roman et al. () considered the comparison between CAF + CTG + Enamel matrix Derivatives (EMD) versus CAF + CTG. The mean VAS Est was 87.0 ± 16 for the test group while 89.5 ± 15 for the control group.…”
Section: Results Of the Analysismentioning
confidence: 99%
“…Individual patient data (IPD) were provided by the author and re‐analysed to obtain mean difference for VAS Est. Roman et al. () considered the comparison between CAF + CTG + Enamel matrix Derivatives (EMD) versus CAF + CTG. The mean VAS Est was 87.0 ± 16 for the test group while 89.5 ± 15 for the control group.…”
Section: Results Of the Analysismentioning
confidence: 99%
“…Sample size calculation for this superiority trial was performed considering root coverage as the primary outcome. The study was powered to detect a significant difference in root recession reduction among four groups ( F test–analysis of variance [ANOVA] for repeated measurements: α = 0.05, power = 80%, effect size = 0.443), based on data from previous studies to calculate the effect size 8,19,20 . A total sample of 60 patients was required in the present trial.…”
Section: Methodsmentioning
confidence: 99%
“…The consensus is that the supplementary use of EMD in root coverage procedures led to improved keratinized tissue and stability of the increased gingival margin level . However, the majority of these clinical studies are of short duration (6‐18 months), with sample sizes limited to no more than 60 teeth . Additionally, the few available longer term studies have shown inconsistent results.…”
Section: Introductionmentioning
confidence: 99%